2011
DOI: 10.1088/0031-9155/56/7/011
|View full text |Cite
|
Sign up to set email alerts
|

Chinese adult anatomical models and the application in evaluation of RF exposures

Abstract: This paper presents the work of constructing Chinese adult anatomical models and their application in evaluation of radio frequency (RF) electromagnetic field exposures. The original dataset was obtained from photos of the sliced frozen cadavers from the Chinese Visible Human Project. Details of preparing the cadaver for slicing procedures which may influence the anatomical structures are discussed. Segmentation and reconstruction were performed mainly manually by experienced anatomists. The reconstructed mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

8
2

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…The CVH has been demonstrated to help individuals master medical imaging technologies. Based on the CVH, virtual human organs and tissues with real anatomical information can be modeled, thereby facilitating 3D visualizations of human anatomy [5–7]. In the present study, we used the cardiac dataset from the first CVH reported by the Computerized Medicine Laboratory of the Third Military Medical University in February 2003 [8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…The CVH has been demonstrated to help individuals master medical imaging technologies. Based on the CVH, virtual human organs and tissues with real anatomical information can be modeled, thereby facilitating 3D visualizations of human anatomy [5–7]. In the present study, we used the cardiac dataset from the first CVH reported by the Computerized Medicine Laboratory of the Third Military Medical University in February 2003 [8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…They were the infant model (representing a 12-month-old, male; Li et al, 2015), Thelonious (representing a 6-year-old male), Billie (representing a 12-year-old male) and Duke (representing a 34-year-old male) from Virtual Family (Christ et al, 2010) and Chinese adult male (representing a 26-year-old male; Wu et al, 2011). With these models, results from different age groups, ethnic groups and physical dimensions could be provided.…”
Section: Human Anatomical Modelsmentioning
confidence: 99%
“…Currently, the most common techniques for performing such simulations are based on the finite-difference time-domain (FDTD) method [1]- [8]; this is primarily due to the method's simplicity and low computational costs. Nevertheless, the FDTD method suffers from well-known accuracy limitations, Manuscript e.g., grid dispersion, approximate truncation of the simulation domain with local boundary conditions, time-domain modeling of dispersive materials, etc.…”
Section: Introductionmentioning
confidence: 99%